Kerangka Teologis Kepemimpinan Dalam Pendidikan Islam - Sukman, Sukman; Chudzaifah, Ibnu (Tarbiyah STAIN Sorong, 2018)
The leader is essentially someone who has the ability to influence the behavior of others in the work by using power. Morally, leadership is closely related to the duties and functions of human beings on this earth. Among the duties and functions of his birth into this world is to preserve and utilize natural resources for the welfare of mankind. Man is created as the caliph of God on earth. In the Qur'an described that a good leader is for the good society as well. In other words, a good society can only be led and only requires a good leader as well. Moral society will determine the moral leader who has high integrity.